Influence of information and communication technologies on academic resilience in vulnerable contexts - Macea-Anaya, Mario; Vargas-Moreno, Jeny; Baena-Navarro, Rubén (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study investigates how the use of information and communication technologies (ICT) influences the academic resilience of high school students in Soacha, Colombia, an area with significant socioeconomic challenges. The objective of the research is to analyze whether greater access to and proper use of ICT can improve students’ ability to face academic and emotional adversities. A mixed methodology was applied, combining quantitative surveys and qualitative interviews with 300 students from three educational institutions, measuring ICT use and academic resilience through validated scales. The findings revealed a significant positive correlation (r=0.95) between ICT use and academic resilience, demonstrating that students who used ICT more frequently showed higher levels of self-efficacy, better stress management, and more efficient academic organization. These results highlight the importance of integrating ICT into educational policies in vulnerable contexts, given their impact on both academic performance and students’ emotional well-being. It is recommended to prioritize digital competence training in educational institutions to strengthen students' abilities to face academic and emotional challenges.